Pengetahuan, Sikap Dan Tindakan Siswi Sekolah Dasar Terkait Genitalia Hygiene - Tetti Solehati; Citra Windani Mambang Sari; Imas Rohimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background:Maintaining genital hygiene is important for females to maintain their reproductive health. Hormonal changes during puberty, vaginal moisture, anatomical location of the vagina and poor genital hygiene can increase the risk of reproductive tract infection, abnormal vaginal discharge, etc. Knowledge, infection, attitude and practice affect genital hygiene behavior amongst adolescents. Objective:This study aimed to identify elementary school students knowledge, attitude and practice towards genital hygiene at administrative area of Jatinangor health center. Method:This study used descriptive quantitative method with a population of elementary school students entering early adolescence (n=721). Samples were recruited using accidental sampling technique consisting grade VI students (n=104). Data were collected using questinnaires which had been tested. Data were analyzed using descriptive analysis. Result:Result showed that 79 respondents (76,0%) had fair knowledge, 56 respondents (53,9%) had a favorable attitude and 55 respondents (52,9%) had a poor practice. Conclusions and Suggestions: the majority of students demostrated poor behavior toward genital hygiene. Sugest for health care staff can increase the awareness of youth by providing reproductive health related information to protect and to maintain reproductive as early is possible.